Fighting Tradition : a Marine's Journey to Justice - Yamashita, Bruce I. (University of Hawaii Press, 2003)
Determined to be a U.S. Marine Corps officer, Bruce Yamashita enrolled in Officer Candidate School, where he was the target of persistent racial harassment by officers and staff. After enduring nine weeks of emotional and physical abuse, Yamashita was "disenrolled" in April 1989--kicked out of the Marine Corps because of the color of his skin. Fighting Tradition is Yamashita's own story of his courageous struggle to expose a pattern of racial discrimination against minorities that has existed at various levels of the Corps. With the support of a broad coalition of community and civil rights organizations, the Hawaii-born law school graduate fought a five-year-long legal, political, and media battle against the military establishment that ended in his commissioning as a captain and the revision of Marine Corps policies and procedures. Fighting Tradition not only is a moving story of personal sacrifice and vision, but contributes also both directly and indirectly to our understanding of the complexities of institutional racism in a politically conservative, demographically shifting society. It is a unique window into the dynamics of race, government, and the law and a stirring reminder of the importance of political mobilization by the individual to achieve justice